Problems of Equality in the Realisation of the Right to Association in Kazakhstan - Mitskaya, Elena; Sarykulov, Kurmangaly; Roisah, Kholis (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
The legal regulation of the constitutional right to freedom of association in Kazakhstan does not fully align with international standards. According to the European Convention on Human Rights, everyone has the right to freedom of association with others, and this right is not necessarily confined to public associations. While the Constitution of Kazakhstan recognizes the right of citizens to freedom of association, it limits this understanding to public associations. Additionally, the right to hold meetings, rallies, and demonstrations is stipulated separately. This study aims to provide a theoretical and legal analysis of Kazakhstan's legal provisions that restrict the right to freedom of association, assess whether the practical implementation of this right in Kazakhstan complies with international human rights standards, and propose measures to eliminate unlawful restrictions. The research employs both normative-legal methods and empirical analysis. The findings indicate that priority changes include amending the Constitution and laws of Kazakhstan to remove the ban on unregistered public associations and explicitly guaranteeing the constitutional right to freedom of association for all individuals, excluding political associations. In conclusion, the study proposes the elimination of unjustified legal barriers to the exercise of the right to freedom of association, which would ensure genuine adherence to this fundamental right.